Sustainable forest management policies in Central Africa. Taking the informal sector into account - Lescuyer, Guillaume; Cerutti, Paolo (Perspective, 2013)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"For 20 years, the Congo Basin countries have been implementing policies aimed at the sustainable management of their forest resources and at poverty reduction. These policies target the major timber concessions, whose production is exported, but overlook the informal small-scale chainsaw milling sector, which supplies domestic and regional markets. Yet this sector has taken the lead in terms of the volume of timber produced and provides jobs and income. At a time when States are increasingly urged to guarantee the legality – or even sustainability – of their production, it is urgent that they implement policies to ensure their small-scale chainsaw milling operations are more sustainable and to formalise the sector."" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"For 20 years, the Congo Basin countries have been implementing policies aimed at the sustainable management of their forest resources and at poverty reduction. These policies target the major timber concessions, whose production is exported, but overlook the informal small-scale chainsaw milling sector, which supplies domestic and regional markets. Yet this sector has taken the lead in terms of the volume of timber produced and provides jobs and income. At a time when States are increasingly urged to guarantee the legality – or even sustainability – of their production, it is urgent that they implement policies to ensure their small-scale chainsaw milling operations are more sustainable and to formalise the sector."" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">For 20 years, the Congo Basin countries have been implementing policies aimed at the sustainable management of their forest resources and at poverty reduction. These policies target the major timber concessions, whose production is exported, but overlook the informal small-scale chainsaw milling sector, which supplies domestic and regional markets. Yet this sector has taken the lead in terms of the volume of timber produced and provides jobs and income. At a time when States are increasingly urged to guarantee the legality – or even sustainability – of their production, it is urgent that they implement policies to ensure their small-scale chainsaw milling operations are more sustainable and to formalise the sector.